Environment and society in the lower Mekong basin : - McElwee, Pamela (Institute for Development Anthropology, 1999)
The review is presented in two volumes. The first volume is a substantive discussion of the region as drawn the literature. It is intended only as a guide to the literature and does not preten to be comprehensive in any of its sections,...